PANDEMIC, HEALTH CRISIS AND INDEMNITY LIABILITY OF HEALTH PROFESSIONALS AND INSTITUTIONS - GIRER, Marion (MEDECINE LEGALE DROIT MEDICAL, 2025)
The health crisis linked to COVID-19 raises legal questions of an unprecedented magnitude concerning the responsibilities linked to contamination by the virus within health care institutions and among health care professionals. The compensation system for victims and their relatives is complex and faces several difficulties, mainly concerning the proof of the origin of the infection, the impact of the previous condition or the exoneration of responsibility and the possible setting up of a compensation fund.